Laser interstitial thermal therapy for NPRL3-related epilepsy with multiple seizure foci: A case report - Abumurad, Sumayyah (Epilepsy Behav Rep, 2021)
Introduction: NPRL3 gene mutations cause autosomal dominant familial focal epilepsy of variable foci (FFEVF) and is characterized by focal epilepsy arising from different brain regions including temporal, frontal, parietal and occipital lobes. About 50% of patients with NPRL3 related epilepsy are resistant to medical treatment. Method: We present a case of 27 years old man with NPRL3 related focal drug-resistant epilepsy. Stereotactic EEG showed two independent seizure foci, namely, left hippocampus and left orbitofrontal cortices. He underwent laser interstitial thermal therapy for ablating both foci in the same procedure that led to seizure cessation. Conclusion: laser interstitial thermal therapy can be an effective treatment for drug resistant NPRL3 related focal epilepsy with better tolerance and less morbidity as compared to open surgical resection, particularly in those with multiple seizure foci.